PENGEMBANGAN FORMULA ENTERAL BERBASIS TEPUNG LABU KUNING (Cucurbita moschata) DAN TEPUNG PUTIH TELUR (Albumen) UNTUK PASIEN GAGAL GINJAL KRONIK PREDIALISIS DEVELOPMENT OF AN ENTERAL FORMULA BASED ON PUMPKIN FLOUR (Cucurbita moschata) AND EGG WHITE FLOUR - Putri, Melani Yuda; Yenny, Moviana (Jurnal Inovasi Bahan Lokal dan Pemberdayaan Masyarakat, 2024)
ABSTRACT This study aims to determine the effect of different formulations of pumpkin flour and egg white flour on the quality of low-protein enteral food for CKD patients "Pumkinsol" including nutrient content, organoleptic properties, flowability, viscosity and shelf life. This type of research is quasi experimental design. The observations carried out included hedonic tests using 30 somewhat trained panelists. The enteral formula selected was formula 1 with a formulation ratio of egg white flour and pumpkin flour of 20%:80% with an average rating of 5.6. Based on the Kruskall Wallis test on the aspects of taste, aroma and consistency, there is no difference between formulas 1, 2 and 3, indicated by a p-value > α 0.05. In this study, it met the low protein requirements for per 100 kcal it contained 2.21 grams of protein. Meanwhile, in the aspect of color and consistency, there are differences between formulas 1, 2 and 3, indicated by a p-value < α 0.05. The suggestion in this research is that in the aroma aspect, use the addition of fresh aroma ingredients such as (lemon or lime) to eliminate the aroma of pumpkin which feels like herbal medicine. Keywords: enteral formula, pumkinsol, CKD, low protein principles.